Post-Harvest Losses Management through Climate Smart Innovations: A collaborative Approach Among Value Chain Actors - Binge, Brenda; Jalango, Dorcas; Tesfaye, Lidya (Accelerating Impacts of CGIAR Climate Research for Africa, 2023)
The report highlights challenges faced by the agricultural sector in Kenya, Ethiopia, and Zambia, including productivity issues and food security concerns due to factors such as limited inputs, market access, and climate-related vulnerabilities. Post-harvest losses (PHL) are identified as a major obstacle for small and medium-sized enterprises (SME) processors, stemming from inadequate infrastructure and poor handling methods. The report emphasizes the impact on resources, income, and food security, proposing innovative solutions such as improved storage technologies and digital agriculture ecosystems to address these challenges and reduce PHL across various value chains. Differential impacts on women and men are noted, with potential for increased resilience through knowledge sharing and capacity building initiatives. The role of digital solutions in enhancing access to information, markets, and localized processing facilities is highlighted as a feasible pathway for reducing post-harvest losses at the local level.